Coronavirus disease 2019 with Chilaiditi sign. Issue 4 (22nd April 2023) - Tominaga, Yoshiteru; Hirayama, Ichiro; Nonaka, Minaho; Yano, Tetsuhiro; Kurihara, Kazuto; Ishii, Mitsuru
Abstract: In patients with the Chilaiditi sign, pulmonary lower lobes collapse occurs because of interposition of the bowel between diaphragm and liver. When such patients suffer from COVID‐19 pneumonia, clinicians should carefully monitor respiratory status. Abstract : A 76‐year‐old man was diagnosed with pneumonia due to coronavirus disease 2019 complicated with Chilaiditi sign. The patient's intestinal tract pushed up against the diaphragm and caused atelectasis of the pulmonary lower lobes, worsening his respiratory condition.